Electrode and preparation method thereof, electrochemical device and electronic device

By performing thermogravimetric analysis on the active material layer of the electrochemical device, its conductivity is adjusted, so as to increase the electrode thickness without affecting the electrode performance and increase the energy density and capacity of the electrochemical device.

CN115398667BActive Publication Date: 2025-02-28NINGDE AMPEREX TECHNOLOGY LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202180026305.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-11-15
Publication Date
2025-02-28
Estimated Expiration
2041-11-15

AI Technical Summary

Technical Problem

While the existing electrochemical devices increase the energy density, it is difficult to increase the thickness of the electrode to increase capacity without affecting the performance of the electrode.

Method used

By performing thermogravimetric analysis on the active material layer at a temperature increase rate of 10°C/min under an inert atmosphere, the difference in the number of thermal weight loss peaks in the first and second regions is adjusted ≥1, thereby improving the conductivity of the active material layer and increasing its thickness.

Benefits of technology

The conductivity of the electrode is improved, so that the energy density and capacity of the electrochemical device can be improved, while maintaining the performance of the electrode.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115398667B_ABST
    Figure CN115398667B_ABST
Patent Text Reader

Abstract

The present application proposes an electrode and a preparation method thereof, an electrochemical device and an electronic device. The electrode includes a current collector and an active material layer located on one or both sides of the current collector; the active material layer includes a first region and a second region, and along the direction of the electrode thickness, the first region is located between the current collector and the second region; the first region is from the current collector side to 2 / 3 of the thickness of the active material layer, and the second region is from 2 / 3 of the thickness of the active material layer to the electrode surface; the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the difference in the number of thermal weight loss peaks between the first region and the second region at 200°C to 800°C is ≥1. This shows that the second region of the active material layer in the present application has good electrical conductivity, so that ions and electrons can be transmitted to the first region through the second region, thereby improving the overall electrical conductivity of the electrode, which is conducive to improving the capacity and energy density of the electrochemical device using the electrode.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application relates to the field of electrochemical energy storage, and in particular to electrodes and preparation methods thereof, electrochemical devices and electronic devices. Background Art

[0002] Electrochemical devices, such as lithium-ion batteries, have the advantages of high energy density, high power, and long cycle life, and are widely used in various fields. With the development of technology, the requirements for the energy density of electrochemical devices are getting higher and higher. In order to improve the energy density of electrochemical devices, some technologies increase the capacity or voltage of active materials, and other technologies increase the content of active materials per unit volume and reduce the content of inactive materials. The proportion of inactive substances can be reduced by reducing the thickness of the current collector or the separator, reducing the proportion of inactive materials in the formula, and preparing thicker electrodes. However, in actual application, the thickness of the current collector and the separator has been reduced to near the limit, so the electrode thickness can only be increased. However, excessive increase in the thickness of the electrode may affect the performance of the electrochemical device, so the thickness of the electrode cannot be significantly increased. Therefore, how to increase the thickness of the electrode as much as possible to increase the capacity of the electrochemical device while ensuring the performance of the electrochemical device is an urgent problem to be solved. Summary of the invention

[0003] Some embodiments of the present application provide an electrode and a method for preparing the same, an electrochemical device and an electronic device, wherein a thermogravimetric analysis of the active material layer is performed at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the difference in the number of thermal weight loss peaks between the first region and the second region is ≥1, thereby improving the conductivity of the second region of the active material layer, which is beneficial to increase the thickness of the active material layer to improve the energy density of the electrochemical device.

[0004] In some embodiments of the present application, an electrode is proposed, including: a current collector and an active material layer located on one or both sides of the current collector; the active material layer includes a first region and a second region, and along the thickness direction of the electrode, the first region is located between the current collector and the second region; the first region is from the current collector side to 2 / 3 of the thickness of the active material layer, and the second region is from 2 / 3 of the thickness of the active material layer to the electrode surface. The active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min in an inert atmosphere. The results of the thermogravimetric analysis show that the difference in the number of thermal weight loss peaks between the first region and the second region at 200°C to 800°C is ≥1. This indicates that the conductivity of the second region is better than that of the first region, which is conducive to electronic conduction.

[0005] In some embodiments of the present application, the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere, and the results of the thermogravimetric analysis show that the number of weight loss peaks in the first region at 200°C to 800°C is not less than 1, and the number of weight loss peaks in the second region at 200°C to 800°C is 0 to 2. This indicates that the second region of the active material layer in the present application has good conductivity, which is beneficial to increase the thickness of the electrode, and further to increase the capacity and energy density of the electrochemical device.

[0006] In some embodiments of the present application, the results of thermogravimetric analysis show that the mass change of the first region from 200°C to 800°C is 0.21% to 13%; the results of thermogravimetric analysis show that the mass change of the second region from 200°C to 800°C is 0% to 2.4%. This shows that the content of the polymer compound in the second region of the active material layer in the present application is zero or very low, which is conducive to improving the ion and electron conduction in the second region of the active material layer, so that ions and electrons can be transmitted to the first region of the active material layer, improving the overall conductivity. In some embodiments, the polymer compound is a binder and / or a thickener. In some embodiments of the present application, the results of thermogravimetric analysis show that the mass change of the first region from 200°C to 800°C is 1.6% to 4.02%.

[0007] In some embodiments of the present application, the electrode is a positive electrode or a negative electrode. In some embodiments, the electrode is a negative electrode, the active material layer is a negative electrode active material layer, and the current collector is a negative electrode current collector. In some embodiments, the compaction density ρ1 of the negative electrode active material layer is ≥ 0.6 g / cm 3 , a higher compaction density is conducive to increasing the energy that can be stored per unit volume of the electrochemical device. In some embodiments, the thickness of the negative electrode active material layer on one side of the negative electrode current collector h1 ≥ 10 μm, and a thicker thickness is conducive to carrying more active materials, thereby improving the energy density of the electrochemical device. In some embodiments, the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon oxide, graphite, silicon or hard carbon.

[0008] In some embodiments of the present application, the electrode is a negative electrode, the active material layer is a negative electrode active material layer, the current collector is a negative electrode current collector, and the compaction density ρ1 of the negative electrode active material layer satisfies: 1.85 g / cm 3 ≥ρ1≥0.65g / cm 3 , which is beneficial to improve the energy density. In some embodiments, the thickness h1 of the negative electrode active material layer on one side of the negative electrode current collector satisfies: 1500 μm ≥ h1 ≥ 15 μm. This is beneficial to prevent the negative electrode active material layer from falling off while improving the energy density.

[0009] In some embodiments of the present application, the compaction density ρ1 of the negative electrode active material layer satisfies: 1.83 g / cm3 ≥ρ1≥1.0g / cm 3 In some embodiments of the present application, the thickness h1 of the negative electrode active material layer on one side of the negative electrode current collector satisfies: 150 μm ≥ h1 ≥ 30 μm.

[0010] In some embodiments of the present application, the electrode is the positive electrode, the current collector is the positive electrode current collector, the active material layer is the positive electrode active material layer, and the compaction density ρ2 of the positive electrode active material layer is ≥2 g / cm 3 , which is conducive to improving energy density. In some embodiments, the thickness h2 of the single-side positive electrode active material layer on the positive electrode current collector is ≥ 20 μm, which is conducive to carrying more positive electrode materials and thus improving capacity. In some embodiments, the positive electrode active material layer includes a positive electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt aluminum oxide.

[0011] In some embodiments of the present application, the electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the compaction density ρ2 of the positive electrode active material layer satisfies: 4.25 g / cm 3 ≥ρ2≥2.3g / cm 3 , thereby improving energy density while avoiding particle crushing. In some embodiments, the thickness h2 of the single-sided positive electrode active material layer on the positive electrode current collector satisfies: 1500μm≥h2≥30μm, thereby improving the battery capacity while preventing the positive electrode active material layer from falling off the current collector. In some embodiments of the present application, the electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the compaction density ρ2 of the positive electrode active material layer satisfies: 4.23g / cm 3 ≥ρ2≥4.0g / cm 3 In some embodiments, the thickness h2 of the positive electrode active material layer on one side of the positive electrode current collector satisfies: 130 μm ≥ h2 ≥ 26 μm.

[0012] In some embodiments of the present application, the active material layer includes a conductive agent, the mass percentage of the conductive agent in the first region is B, the mass percentage of the conductive agent in the second region is A, A is greater than B, thereby improving the conductivity of the second region, so that ions and electrons can be transmitted to the first region. In some embodiments, the mass percentage of the conductive agent in the first region is B, and the mass percentage of the conductive agent in the second region is A, (A-B) / B≥20%. In some embodiments, the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black or conductive carbon black. In some embodiments, based on the total mass of the active material layer, the mass percentage of the conductive agent in the active material layer is 0% to 2%.

[0013] In some embodiments of the present application, the first region includes a polymer compound, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber. In some embodiments, the mass percentage of the polymer compound in the active material layer is 0.42% to 14%. In some embodiments, the mass percentage of the polymer compound in the active material layer is 2.0% to 5.0%.

[0014] In some embodiments of the present application, a method for preparing an electrode is proposed, which can be used to manufacture any electrode in the present application, comprising: coating a slurry of an active material layer on at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode comprises: plasma treating the initial electrode in a vacuum environment, the plasma power is 0.5kW to 5kW, the gas source comprises at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate is 3000sccm to 5000sccm, the temperature is 20°C to 60°C, and the treatment time is 0.5min to 1min; or, heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature is greater than 200°C, and the heat treatment time is 1min to 3min; or, laser bombarding the initial electrode in a vacuum or inert gas environment, the laser intensity is 30W to 100W, and the treatment time is 0.5s to 1s.

[0015] In some embodiments of the present application, a method for preparing an electrode is proposed, which can be used to manufacture any electrode in the present application, including: applying a slurry of an active material layer to at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode includes: heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature is 350°C to 600°C, and the heat treatment time is 1min to 3min. In some embodiments of the present application, an electrochemical device is proposed, including an electrode; the electrode is any electrode in the present application; or, the electrode is an electrode prepared by the preparation method proposed in the present application.

[0016] In some embodiments of the present application, an electronic device is provided, including the electrochemical device provided in the present application.

[0017] An electrode proposed in an embodiment of the present application includes a current collector and an active material layer located on one or both sides of the current collector; the active material layer includes a first region and a second region, the first region is located between the current collector and the second region; the first region is along the thickness direction, from the current collector side to the 2 / 3 thickness of the active material layer, and the second region is along the thickness direction, from the 2 / 3 thickness of the active material layer to the electrode surface. The active material layer was subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere. The results of the thermogravimetric analysis showed that the difference in the number of thermal weight loss peaks between the first region and the second region at 200°C to 800°C was ≥1. This shows that the second region of the active material layer in the present application has good electrical conductivity, so that ions and electrons can be transmitted to the first region through the second region, thereby improving the overall electrical conductivity of the electrode, which is conducive to increasing the thickness of the electrode, and then to increasing the capacity and energy density of the electrochemical device using the electrode. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The above and other features, advantages and aspects of the embodiments of the present application will become more apparent with reference to the following detailed description in conjunction with the accompanying drawings. Throughout the accompanying drawings, the same or similar reference numerals represent the same or similar elements. It should be understood that the drawings are schematic and that components and elements are not necessarily drawn to scale.

[0019] Figure 1 It is a schematic diagram of an electrode according to an embodiment of the present application. DETAILED DESCRIPTION

[0020] The following embodiments may enable those skilled in the art to more fully understand the present application, but do not limit the present application in any way.

[0021] In order to improve the energy density of electrochemical devices, some technologies increase the energy density of electrochemical devices by increasing the thickness of the active material layer in the electrode. However, increasing the thickness of the active material layer in the electrode may deteriorate the conductivity of the active material layer due to the excessive thickness of the active material layer. In order to improve the conductivity of the active material layer, some technologies use a multi-layer active material layer structure, but the composite cold pressing process of multiple single-layer structures is complicated, and it is impossible to avoid the change of the original compaction density and porosity of each single layer during the cold pressing process again, and the joints between the layers are prone to delamination due to loose bonding, which affects the conduction of electrons and ions and deteriorates the cycle performance. In other technologies, lasers are used to punch holes in the active material layer, but laser drilling is inefficient, costly, and energy density is easily lost during the drilling process. In other technologies, a pore-forming agent solution is applied to the electrode surface, but this cannot avoid the dissolution of the electrode surface, and the depth of the holes formed by the pore-forming agent is limited, which has limited improvement on the near-current collector side. The above technologies solve the problem of ion transport from electrolyte to the surface of active material through different methods, but the ion transport from the surface of active material to the inside of active material layer remains unchanged, the obstacle of ion transport still exists, and the improvement effect is not good.

[0022] Some embodiments of the present application provide an electrode that can improve the conductivity of the active material layer of the electrode, thereby facilitating the improvement of the energy density of the electrochemical device. In some embodiments, an electrode, which can be an electrode of an electrochemical device, includes a current collector and an active material layer located on one or both sides of the current collector; the active material layer includes a first region and a second region, and along the thickness direction of the electrode, the first region is located between the current collector and the second region; the first region is from the current collector side to 2 / 3 of the thickness of the active material layer, and the second region is from 2 / 3 of the thickness of the active material layer to the electrode surface, and the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min in an inert atmosphere, and the results of the thermogravimetric analysis show that the difference in the number of thermal weight loss peaks between the first region and the second region at 200°C to 800°C is ≥1. In some embodiments, the thickness of the first region accounts for 2 / 3 of the total thickness of the active material layer, and the thickness of the second region accounts for 1 / 3 of the total thickness of the active material layer. The number of weight loss peaks in the second region is less than that in the first region, indicating that the types or contents of polymer compounds contained in the second region are less than those in the first region. This is beneficial to the conductivity of the second region, thereby facilitating the transmission of electrons through the second region to the first region, thereby improving the overall conductivity of the electrode.

[0023] In some embodiments of the present application, the active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere. The results of the thermogravimetric analysis show that the number of weight loss peaks in the first region from 200°C to 800°C is not less than 1, and the number of weight loss peaks in the second region from 200°C to 800°C is 0 to 2. In some embodiments, the second region is located on the side of the first region away from the current collector, and the transmission of ions and electrons needs to pass through the second region. Therefore, the conductivity of the second region has a greater influence on the conductivity of the electrode. In the embodiment of the present application, the number of weight loss peaks in the second region from 200°C to 800°C is 0 to 2, which indicates that the second region does not have a polymer compound or has a very low content of a polymer compound, such as a polymer thickener and a binder. This can avoid the influence of the polymer compound in the active material layer on the conductivity of the second region of the active material layer, thereby improving the overall conductivity of the active material layer for ions and electrons. In this way, when the thickness of the active material layer is increased to increase the energy density of the electrochemical device, the active material layer has good conductivity, so the electrical performance of the electrochemical device will not be deteriorated due to the increase in the thickness of the active material layer. On the other hand, in the present application, the number of weight loss peaks in the first region of the active material layer at 200°C to 800°C is not less than 1, which indicates that there is a polymer compound in the first region of the active material layer of the present application, because the polymer compound is required in the active material layer to make the substances in the active material layer bond to each other and attach to the current collector. It can be seen that the electrochemical device proposed in the embodiment of the present application is beneficial to the performance of the electrochemical device and to improve the energy density because the active material layer has good conductivity, and the thickness of the first region and the second region is limited in the present application, because if the thickness of the second region is too small, the improvement of the conductivity of the active material layer is not obvious, if the thickness of the second region is too large, the active material layer may fall off during rolling, the thickness of the first region is too small, the overall capacity of the active material layer may be insufficient, and the thickness of the first region is too large, which may cause the bonding force between the active material layer and the current collector to be insufficient, and it is difficult to carry the active material layer.

[0024] In some embodiments of the present application, the results of thermogravimetric analysis show that the mass change of the first region from 200°C to 800°C is 0.21% to 13%. In some embodiments, the results of thermogravimetric analysis show that the mass change of the second region from 200°C to 800°C is 0% to 2.4%. In some embodiments, the detection accuracy of the thermogravimetric analysis device is 0.2%. In this embodiment, the mass change of the second region of the active material layer from 200°C to 800°C is low, which indicates that the content of the polymer compound in the second region of the active material layer in the present application is zero or extremely low, which is conducive to improving the ion and electron conduction in the second region of the active material layer, thereby improving the electrical performance of the electrochemical device, and the content of the polymer compound in the first region is not zero, which is conducive to ensuring the overall polymerization force of the active material layer and the bonding force with the current collector. In some embodiments, the results of thermogravimetric analysis show that the mass change of the first region from 200°C to 800°C is 1.6% to 4.02%. In some embodiments, the polymer compound is a binder and / or a thickener, and the content of the binder and / or the thickener in the second region is almost zero to ensure electrical conductivity.

[0025] In some embodiments of the present application, the electrode is a negative electrode or a positive electrode, and can be a negative electrode or a positive electrode of an electrochemical device. In some embodiments, the electrode is a negative electrode, the active material layer is a negative electrode active material layer, and the current collector is a negative electrode current collector. The current collector can be copper foil, aluminum foil, steel foil, etc., without limitation. In some embodiments, the compaction density ρ1 of the negative electrode active material layer is ≥0.6 g / cm 3 , a higher compaction density indicates that the mass of the active material layer carried by the electrode per unit volume is greater. The greater the mass of the negative electrode active material layer, the more energy that can be stored per unit volume of the electrochemical device, thereby increasing the energy density. In some embodiments, the compaction density ρ1 of the active material layer satisfies: 1.85 g / cm 3 ≥ρ1≥0.65g / cm 3 In some embodiments, 1.83 g / cm 3 ≥ρ1≥1.0g / cm 3 , which is beneficial to improve the energy density of the electrochemical device. In some embodiments, by limiting the compaction density of the negative electrode active material layer to not less than 1.0 g / cm 3 The energy density of the electrochemical device can be further guaranteed, while the compaction density of the negative electrode active material layer is limited to no more than 1.83 g / cm 3 It can prevent the particles in the active material layer from breaking due to excessive compaction density, thereby increasing the consumption of the electrolyte and deteriorating the cycle performance.

[0026] In some embodiments of the present application, the thickness h1 of the single-sided negative electrode active material layer on the negative electrode current collector is ≥10μm; in some embodiments, a thicker negative electrode active material layer is beneficial to increase the proportion of the negative electrode active material layer in the electrochemical device, thereby increasing the energy density of the electrochemical device. In some embodiments of the present application, the thickness h1 of the single-sided negative electrode active material layer on the negative electrode current collector satisfies: 1500μm ≥1h ≥15μm, and in some embodiments, 150μm ≥h1 ≥30μm. By limiting the thickness of the negative electrode active material layer to not less than 30μm, the thickness of the negative electrode active material layer can be ensured, thereby increasing the overall energy density of the electrochemical device. By limiting the thickness of the negative electrode active material layer to not more than 150μm, the problem of separation between the negative electrode active material layer and the current collector that may occur due to the negative electrode active material layer being too thick can be prevented.

[0027] In some embodiments of the present application, the negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon oxide, graphite or hard carbon.

[0028] In some embodiments of the present application, the electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the compaction density ρ2 of the positive electrode active material layer is ≥2 g / cm 3 , limiting the compaction density of the positive electrode active material layer can improve the energy density. Optionally, the compaction density ρ2 of the positive electrode active material layer satisfies: 4.25 g / cm 3 ≥ρ2≥2.3g / cm 3 In some embodiments, 4.23 g / cm 3 ≥ρ2≥4.0g / cm 3 By further limiting the compaction density of the positive electrode active material layer, the energy density can be further improved, and the problem of material particle breakage and insufficient electrolyte infiltration caused by excessive compaction density can be prevented.

[0029] In some embodiments of the present application, the thickness of the single-sided positive electrode active material layer on the positive electrode current collector h2≥20μm. In some embodiments, by increasing the thickness of the single-sided positive electrode active material on the positive electrode current collector, the positive electrode can carry more active materials, thereby increasing the capacity. In some embodiments, the thickness of the single-sided positive electrode active material layer on the positive electrode current collector h2 satisfies: 1500μm≥h2≥30μm. In some embodiments, 130μm≥h2≥26μm. By further limiting the thickness of the positive electrode active material layer, the positive electrode active material layer can be prevented from being too thick and desorbed from the positive electrode current collector while increasing the capacity.

[0030] In some embodiments of the present application, the positive electrode active material layer includes a positive electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide, and lithium nickel cobalt aluminum oxide. The positive electrode material may include a combination of two or more thereof.

[0031] In some embodiments of the present application, the active material layer includes a conductive agent, the mass percentage of the conductive agent in the first region is B, the mass percentage of the conductive agent in the second region is A, and A is greater than B. In some embodiments, the second region is located on a side of the first region away from the current collector, so the content of the conductive agent in the second region is increased to improve the conductive performance and enable ions and electrons to be conducted into the active material layer.

[0032] In some embodiments of the present application, the mass percentage of the conductive agent in the first region is B, the mass percentage of the conductive agent in the second region is A, and (A-B) / B≥20%. In some embodiments, the mass percentage of the conductive agent in the second region is significantly higher than that in the second region, because the second region is closer to the outside of the active material layer, and the transmission path of ions and electrons needs to pass through the second region. Therefore, when the mass percentage of the conductive agent in the second region is more than 20% higher than that in the first region, the conductivity of the first region can be guaranteed.

[0033] In some embodiments of the present application, the conductive agent includes at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black, or conductive carbon black. In some embodiments of the present application, the mass percentage of the conductive agent in the active material layer is 0% to 2% based on the total mass of the active material layer. The carbon nanotubes in the conductive agent can be single-walled carbon nanotubes or multi-walled carbon nanotubes, which can increase long-range electron conduction.

[0034] In some embodiments of the present application, the first region includes a polymer compound, the polymer compound may include a binder and / or a thickener, and the polymer compound includes at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber;

[0035] In some embodiments of the present application, the mass percentage of the polymer compound in the active material layer is 0.42% to 14%, and in some embodiments, the mass percentage of the polymer compound in the active material layer is 2.0% to 5.0%. Too low a mass percentage of the polymer compound may result in insufficient adhesion between the active material layer and the current collector, and too high a mass percentage of the adhesion may affect the conductivity of the active material layer.

[0036] In some embodiments of the present application, the polymer compound is distributed in a point-like or surface-like manner on the surface of the active material (e.g., the negative electrode material) of the active material layer, and is concentrated on the surface of the active material or between the particles of the active material. The active material is more exposed, which has little hindrance to the transmission of electrons and ions, and is beneficial to ensuring conductivity.

[0037] In some embodiments of this application, please refer to Figure 1 The electrode includes a current collector 10 and an active material layer, the active material layer includes a first region and a second region, the active material layer includes an active material 20 (which can be a positive electrode material or a negative electrode material), a conductive agent 30 and a polymer compound 40, wherein the active material 20 can include a first active material and a second active material, the particle size of the first active material is larger than the particle size of the second active material, and the gap is fully filled by adapting the active materials of different particle sizes.

[0038] In some embodiments of the present application, the electronic conduction in the second region is improved by increasing the mass percentage of the conductive agent in the second region, and the barrier to ion transport is reduced and the electrode kinetics is improved by reducing the content of the polymer compound (such as a binder and / or a thickener) in the second region.

[0039] In some embodiments of the present application, a method for preparing an electrode is provided, which can be used to prepare any electrode of the present application, comprising: applying a slurry of an active material layer to at least one surface of a current collector, drying, and cold pressing to obtain an initial electrode; treating the initial electrode to obtain an electrode; wherein treating the initial electrode comprises: performing plasma treatment on the initial electrode under a vacuum environment, wherein the plasma power is 0.5 kW to 5 kW, the gas source comprises at least one of nitrogen, argon, or carbon tetrafluoride, the gas flow rate is 3000 sccm to 5000 sccm, the temperature is 20° C. to 60° C., and the treatment time is 0.5 min to 1 min;

[0040] Alternatively, the initial electrode is heat treated in a vacuum or inert gas environment, the heat treatment temperature is greater than 200°C, and the heat treatment time is 1 min to 3 min; or, the initial electrode is laser bombarded in a vacuum or inert gas environment, the laser intensity is 30 W to 100 W, and the treatment time is 0.5 s to 1 s.

[0041] In an embodiment of the present application, the initial electrode is processed to remove the polymer compound in the second region of the surface layer of the active material layer of the initial electrode, for example, the binder and / or thickener in the second region is removed, so that the prepared electrode has better conductivity, reduces the coating area of ​​the active material by the polymer compound, reduces the ion conduction barrier, and improves the kinetic performance, which is beneficial to increase the thickness of the active material layer without reducing the electrode performance.

[0042] In some embodiments of the present application, a method for preparing the above-mentioned electrode is proposed, comprising:

[0043] The slurry of the active material layer is coated on at least one surface of the current collector, dried, and cold pressed to obtain an initial electrode; the initial electrode is treated to obtain an electrode; wherein the treatment of the initial electrode includes: heat treating the initial electrode in a vacuum or inert gas environment, the heat treatment temperature is 350°C to 600°C, and the heat treatment time is 1min to 3min.

[0044] In some embodiments of the present application, an electrochemical device is provided, comprising an electrode; the electrode is any electrode of the present application; or, the electrode is an electrode prepared by the preparation method provided in the present application.

[0045] In some embodiments of the present application, the electrochemical device includes a positive electrode, a negative electrode, and a separator disposed between the positive electrode and the negative electrode. In some embodiments, the negative electrode and the positive electrode can be any of the above electrodes. In some embodiments, the current collector of the positive electrode can be Al foil, and of course, other current collectors commonly used in the art can also be used.

[0046] In some embodiments, the separator includes at least one of polyethylene, polypropylene, polyvinylidene fluoride, polyethylene terephthalate, polyimide or aramid. For example, polyethylene includes at least one selected from high-density polyethylene, low-density polyethylene or ultra-high molecular weight polyethylene. In particular, polyethylene and polypropylene have a good effect on preventing short circuits and can improve the stability of the battery through the shutdown effect. In some embodiments, the thickness of the separator is in the range of about 5 μm to 50 μm.

[0047] In some embodiments, the surface of the isolation membrane may further include a porous layer, the porous layer is disposed on at least one surface of the isolation membrane, the porous layer includes inorganic particles and a binder, the inorganic particles are selected from at least one of aluminum oxide (Al2O3), silicon oxide (SiO2), magnesium oxide (MgO), titanium oxide (TiO2), hafnium dioxide (HfO2), tin oxide (SnO2), cerium dioxide (CeO2), nickel oxide (NiO), zinc oxide (ZnO), calcium oxide (CaO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), silicon carbide (SiC), boehmite, aluminum hydroxide, magnesium hydroxide, calcium hydroxide or barium sulfate. In some embodiments, the pores of the isolation membrane have a diameter in the range of about 0.01 μm to 1 μm. The binder of the porous layer is selected from at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride and hexafluoropropylene, polyamide, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, sodium carboxymethyl cellulose, polyvinylpyrrolidone, polyvinyl ether, polymethyl methacrylate, polytetrafluoroethylene or polyhexafluoropropylene. The porous layer on the surface of the separator can improve the heat resistance, oxidation resistance and electrolyte wetting performance of the separator, and enhance the adhesion between the separator and the pole piece.

[0048] In some embodiments of the present application, the electrochemical device may be wound or stacked. In some embodiments, the positive electrode and / or negative electrode of the electrochemical device may be a multilayer structure formed by winding or stacking, or a single-layer structure in which a single-layer positive electrode, a separator, and a single-layer negative electrode are stacked.

[0049] In some embodiments, the electrochemical device includes a lithium ion battery, but the present application is not limited thereto. In some embodiments, the electrochemical device may further include an electrolyte. The electrolyte may be one or more of a gel electrolyte, a solid electrolyte, and an electrolyte, the electrolyte including a lithium salt and a non-aqueous solvent. The lithium salt is selected from one or more of LiPF6, LiBF4, LiAsF6, LiClO4, LiB(C6H5)4, LiCH3SO3, LiCF3SO3, LiN(SO2CF3)2, LiC(SO2CF3)3, LiSiF6, LiBOB or lithium difluoroborate. For example, the lithium salt is selected from LiPF6 because it has high ionic conductivity and can improve cycle characteristics.

[0050] The non-aqueous solvent may be a carbonate compound, a carboxylate compound, an ether compound, other organic solvents or a combination thereof. The carbonate compound may be a linear carbonate compound, a cyclic carbonate compound, a fluorinated carbonate compound or a combination thereof.

[0051] Examples of chain carbonate compounds are diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), methyl ethyl carbonate (MEC) and combinations thereof. Examples of cyclic carbonate compounds are ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate (BC), vinyl ethylene carbonate (VEC) or combinations thereof. Examples of fluorocarbonate compounds are fluoroethylene carbonate (FEC), 1,2-difluoroethylene carbonate, 1,1-difluoroethylene carbonate, 1,1,2-trifluoroethylene carbonate, 1,1,2,2-tetrafluoroethylene carbonate, 1-fluoro-2-methylethylene carbonate, 1-fluoro-1-methylethylene carbonate, 1,2-difluoro-1-methylethylene carbonate, 1,1,2-trifluoro-2-methylethylene carbonate, trifluoromethylethylene carbonate or combinations thereof.

[0052] Examples of the carboxylic acid ester compound are methyl acetate, ethyl acetate, n-propyl acetate, tert-butyl acetate, methyl propionate, ethyl propionate, propyl propionate, γ-butyrolactone, decanolide, valerolactone, mevalonolactone, caprolactone, methyl formate, or a combination thereof.

[0053] Examples of the ether compound are dibutyl ether, tetraglyme, diglyme, 1,2-dimethoxyethane, 1,2-diethoxyethane, ethoxymethoxyethane, 2-methyltetrahydrofuran, tetrahydrofuran, or a combination thereof.

[0054] Examples of other organic solvents are dimethyl sulfoxide, 1,2-dioxolane, sulfolane, methyl sulfolane, 1,3-dimethyl-2-imidazolidinone, N-methyl-2-pyrrolidone, formamide, dimethylformamide, acetonitrile, trimethyl phosphate, triethyl phosphate, trioctyl phosphate, and phosphoric acid esters or combinations thereof.

[0055] In some embodiments of the present application, taking a lithium-ion battery as an example, a positive electrode, a separator, and a negative electrode are wound or stacked in sequence to form an electrode component, and then encapsulated in, for example, an aluminum-plastic film, injected with an electrolyte, formed, and encapsulated to form a lithium-ion battery. Then, the prepared lithium-ion battery is subjected to a performance test.

[0056] Those skilled in the art will appreciate that the above-described method for preparing an electrochemical device (eg, a lithium-ion battery) is only an example, and other methods commonly used in the art may be used without departing from the disclosure of the present application.

[0057] The present application proposes an electronic device, including an electrochemical device; the electrochemical device is an electrochemical device of any one of the present application. The electronic device of the embodiment of the present application is not particularly limited, and it can be any electronic device known in the prior art. In some embodiments, the electronic device may include, but is not limited to, a laptop computer, a pen-input computer, a mobile computer, an e-book player, a portable phone, a portable fax machine, a portable copier, a portable printer, a head-mounted stereo headset, a video recorder, an LCD TV, a portable cleaner, a portable CD player, a mini disc, a transceiver, an electronic notepad, a calculator, a memory card, a portable recorder, a radio, a backup power supply, a motor, a car, a motorcycle, a power bicycle, a bicycle, a drone, a lighting fixture, a toy, a game console, a clock, an electric tool, a flashlight, a camera or a large household battery, etc.

[0058] Some specific embodiments and comparative examples are listed below to better illustrate the present application, wherein a lithium-ion battery is used as an example.

[0059] Example 1

[0060] Preparation of positive electrode sheet: Mix positive electrode materials lithium cobalt oxide, polyvinylidene fluoride (PVDF), and carbon nanotubes (CNT) in a mass ratio of 97.5:1.5:1.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into slurry, and stir evenly to form slurry of positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained after drying.

[0061] Preparation of negative electrode sheets: negative electrode material graphite, conductive agent carbon nanotubes, and binder (styrene acrylate and lithium carboxymethyl cellulose) are mixed in a preset mass ratio, deionized water is used as solvent, to form a negative electrode active material layer slurry, copper foil is used as the negative electrode current collector, the slurry of the negative electrode active material layer is coated on the negative electrode current collector, and dried at 90°C. The dried electrode sheet is heat treated at a heat treatment temperature of 350°C and a heat treatment time of 2 minutes to obtain a negative electrode sheet after heat treatment.

[0062] Preparation of isolation film: The isolation film is 8 μm thick polyethylene (PE).

[0063] Preparation of electrolyte: In an environment with a water content of less than 10 ppm, lithium hexafluorophosphate and a non-aqueous organic solvent (ethylene carbonate (EC): diethyl carbonate (DEC): propylene carbonate (PC): propyl propionate (PP): vinylene carbonate (VC) = 20:30:20:28:2, weight ratio) are prepared in a weight ratio of 8:92 to form an electrolyte.

[0064] Preparation of lithium-ion battery: stack the positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is between the positive electrode sheet and the negative electrode sheet to play an isolating role, and wind them to obtain the electrode assembly. Place the electrode assembly in the outer packaging aluminum plastic film, remove moisture at 80°C, inject the above electrolyte and package, and obtain the lithium-ion battery through the process of formation, degassing, trimming, etc.

[0065] The relevant parameters of Example 1 are as follows: the positive electrode active material layer includes lithium cobalt oxide, PVDF and CNT, and the mass percentages are 97.5%, 1.5% and 1% respectively; the thickness of the positive electrode active material layer on one side of the positive electrode current collector is 63 μm; the compaction density of the positive electrode active material layer on one side of the positive electrode current collector is 4.1 g / cm 3 The negative electrode active material layer includes graphite, styrene acrylate, carboxymethyl cellulose lithium and CNT, with mass percentages of 97.4%, 1%, 1% and 0.6% respectively, and the compaction density of the negative electrode active material layer is 1.74g / cm 3 The thickness of the negative active material layer on one side of the negative current collector is 75μm, the negative electrode material is graphite, the thickness of the first region of the negative active material layer is 50μm, and the thickness of the second region of the negative active material layer is 25μm. The mass percentage A of the conductive agent in the second region of the negative electrode is 0.6%, and the mass percentage B of the conductive agent in the first region of the negative electrode is 0.4%. The negative electrode conductive agent is carbon nanotubes, and the binder in the first region of the negative electrode is styrene acrylate. The mass percentage of the binder in the first region of the negative electrode is 2.5%. The number of thermogravimetric weight loss peaks of the first region of the negative active material layer at 200℃ to 800℃ is 1, and the mass change of the first region of the negative electrode is 1.6%. The number of thermogravimetric weight loss peaks of the second region of the negative active material layer at 200℃ to 800℃ is 0, and the mass change of the second region of the negative electrode is 0.1%.

[0066] Other embodiments 2 to 36 are based on the steps of embodiment 1 with parameter changes, and the specific changed parameters are shown in the table below.

[0067] Embodiment 37:

[0068] Preparation of positive electrode sheet: Mix positive electrode materials lithium cobalt oxide, polyvinylidene fluoride (PVDF), and carbon nanotubes (CNT) in a mass ratio of 97.5:1.5:1.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into slurry, and stir evenly to form a slurry of positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil, dried at 90°C, and the dried electrode sheet is heat treated at a heat treatment temperature of 350°C and a heat treatment time of 2 minutes. After heat treatment, the positive electrode sheet is obtained.

[0069] Preparation of negative electrode sheets: The negative electrode material graphite, the conductive agent carbon nanotubes, and the binder (styrene acrylate and lithium carboxymethyl cellulose) are mixed in a preset mass ratio, deionized water is used as the solvent, a negative electrode active material layer slurry is formed, copper foil is used as the negative electrode current collector, the slurry of the negative electrode active material layer is coated on the negative electrode current collector, and dried at 90°C to obtain the negative electrode sheet.

[0070] The remaining steps of Example 37 are the same as those of Example 1.

[0071] The relevant parameters of Example 37 are as follows: the positive electrode active material layer includes lithium cobalt oxide, PVDF and CNT, and the mass percentages are 97.5%, 1.5% and 1% respectively; the thickness of the positive electrode active material layer on one side of the positive electrode current collector is 63 μm; the compaction density of the positive electrode active material layer on one side of the positive electrode current collector is 4 g / cm 3 The thickness of the first region of the positive electrode active material layer is 42μm, and that of the second region of the positive electrode active material layer is 21μm. The mass percentage A of the conductive agent in the second region of the positive electrode is 1%, and the mass percentage B of the conductive agent in the first region of the positive electrode is 0.67%. The positive electrode conductive agent is carbon nanotubes, and the binder in the first region of the positive electrode is PVDF. The mass percentage of the binder in the first region of the positive electrode is 1.5%. The number of thermogravimetric weight loss peaks of the first region of the positive electrode active material layer at 200℃ to 800℃ is 1, and the mass change of the first region of the positive electrode is 1.2%. The number of thermogravimetric weight loss peaks of the second region of the positive electrode active material layer at 200℃ to 800℃ is 0, and the mass change of the second region of the positive electrode is 0.1%.

[0072] The negative electrode active material layer includes graphite, styrene acrylate, carboxymethyl cellulose lithium and CNT, with mass percentages of 97.4%, 1%, 1% and 0.6% respectively, and the compaction density of the negative electrode active material layer is 1.74g / cm 3 The thickness of the negative electrode active material layer on one side of the negative electrode current collector is 73 μm, and the negative electrode material is graphite.

[0073] Other embodiments 38 to 48 are based on the steps of embodiment 34 with parameter changes, and the specific changed parameters are shown in the table below.

[0074] Embodiment 49

[0075] Preparation of positive electrode sheet: Mix positive electrode materials lithium cobalt oxide, polyvinylidene fluoride (PVDF), and carbon nanotubes (CNT) in a mass ratio of 97.5:1.5:1.0, use N-methylpyrrolidone (NMP) as a solvent, prepare into slurry, and stir evenly to form a slurry of positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil, dried at 90°C, and the dried electrode sheet is heat treated at a heat treatment temperature of 350°C and a heat treatment time of 2 minutes. After heat treatment, the positive electrode sheet is obtained.

[0076] Preparation of negative electrode sheets: negative electrode material graphite, conductive agent carbon nanotubes, and binder (styrene acrylate and lithium carboxymethyl cellulose) are mixed in a preset mass ratio, deionized water is used as solvent, to form a negative electrode active material layer slurry, copper foil is used as the negative electrode current collector, the slurry of the negative electrode active material layer is coated on the negative electrode current collector, and dried at 90°C. The dried electrode sheet is heat treated at a heat treatment temperature of 350°C and a heat treatment time of 2 minutes to obtain a negative electrode sheet after heat treatment.

[0077] The remaining steps of Example 49 are the same as those of Example 1.

[0078] The relevant parameters of Example 49 are as follows: the positive electrode active material layer includes lithium cobalt oxide, PVDF and CNT, and the mass percentages are 97.5%, 1.5% and 1% respectively; the thickness of the positive electrode active material layer on one side of the positive electrode current collector is 63 μm; the compaction density of the positive electrode active material layer on one side of the positive electrode current collector is 4.1 g / cm 3 The thickness of the first region of the positive electrode active material layer is 42 μm, the thickness of the second region of the positive electrode active material layer is 21 μm, the mass percentage of the conductive agent in the second region of the positive electrode A is 1%, the mass percentage of the conductive agent in the first region of the positive electrode B is 0.67%, the positive electrode conductive agent is carbon nanotubes, the binder in the first region of the positive electrode is PVDF, the mass percentage of the binder in the first region of the positive electrode is 1.5%, the number of thermogravimetric weight loss peaks of the first region of the positive electrode active material layer at 200°C to 800°C is 1, and the mass change of the first region of the positive electrode is 1.2%, the number of thermogravimetric weight loss peaks of the second region of the positive electrode active material layer at 200°C to 800°C is 0, and the mass change of the second region of the positive electrode is 0.1%. The negative electrode active material layer includes graphite, styrene acrylate, carboxymethyl cellulose lithium and CNT, and the mass percentages are 97.4%, 1%, 1% and 0.6% respectively, and the compaction density of the negative electrode active material layer is 1.74 g / cm 3The thickness of the negative active material layer on one side of the negative current collector is 75 μm, the negative electrode material is graphite, the thickness of the first region of the negative active material layer is 50 μm, and the thickness of the second region of the negative active material layer is 25 μm. The mass percentage A of the conductive agent in the second region of the negative electrode is 0.6%, and the mass percentage B of the conductive agent in the first region of the negative electrode is 0.4%. The negative electrode conductive agent is carbon nanotubes, and the binder in the first region of the negative electrode is styrene acrylate and lithium carboxymethyl cellulose. The mass ratio of the two binders is 1:1, and the mass percentage of the binder in the first region of the negative electrode is 2%. The number of thermal gravimetric weight loss peaks of the first region of the negative active material layer at 200°C to 800°C is 2, and the mass change of the first region of the negative electrode is 1.6%, the number of thermal gravimetric weight loss peaks of the second region of the negative active material layer at 200°C to 800°C is 0, and the mass change of the second region of the negative electrode is 0.1%.

[0079] Comparative Example 1

[0080] Preparation of positive electrode sheet: The positive electrode material lithium cobalt oxide, the binder PVDF and the conductive agent carbon nanotube are mixed in a mass ratio of 97.5%:1.5%:1%, and N-methylpyrrolidone (NMP) is used as a solvent to prepare a slurry, which is then stirred evenly to form a slurry of the positive electrode active material layer. The slurry is evenly coated on the positive electrode current collector aluminum foil, and dried at 90°C to obtain a positive electrode sheet.

[0081] Preparation of negative electrode sheet: negative electrode material graphite, binder styrene acrylate, binder carboxymethyl cellulose lithium, and conductive agent CNT are mixed in the ratio of 97.5%:1%:1%:0.5%, deionized water is used as solvent to form a negative electrode active material layer slurry, copper foil is used as the negative electrode current collector, the slurry of the negative electrode active material layer is coated on the negative electrode current collector, and dried at 90°C to obtain a negative electrode sheet.

[0082] The remaining preparation steps of Comparative Example 1 are the same as those of Example 1. The differences in parameters between Comparative Example 1 and Example 1 are shown in the table below.

[0083] Other comparative examples 2 to 3 are based on the steps of comparative example 1 with parameter changes, and the specific changed parameters are shown in the table below.

[0084] The test methods of the present application are described below.

[0085] 1. Thermogravimetric test

[0086] The battery was discharged to 3.0V, and the battery was disassembled to obtain the negative electrode plate. The plate was soaked in DMC (dimethyl carbonate) for 12 to 24 hours, and then the DMC was replaced and soaked for another 12 to 24 hours, and dried at 80°C to 100°C. The active material layer powder at the corresponding position was scraped from the surface of the plate for testing. The active material layer of the negative electrode of the prepared lithium-ion battery was determined by thermogravimetric analysis, and the mass change and the number of weight loss peaks during the thermogravimetric analysis were tested. The test range was 200°C to 800°C, the heating rate was 10°C / min, and the test atmosphere was an inert atmosphere.

[0087] 2. Resistivity test

[0088] The resistivity of the active material layer is tested using a resistance tester. The upper and lower plane controllable pressure probes are used to directly measure the electrode. An alternating current is loaded to the test positive electrode or negative electrode. At the same time, a certain pressure (0.35T) is applied to the test active material layer to obtain the overall resistance in the thickness direction of the electrode. At the same time, the area (A) and thickness (l) of the tested electrode are collected, and the resistivity of the tested electrode is derived according to the resistivity calculation formula (ρ=R*A / l).

[0089] 3. AC resistance test

[0090] A small 1Khz AC current is applied to the positive and negative electrodes of the battery, and the AC resistance of the battery is obtained by measuring the voltage response.

[0091] 4. 25℃ DC resistance DCR test

[0092] At 25°C, charge the lithium-ion battery to 4.45V at 0.5C, then charge to 0.05C at constant voltage; let stand for 30 minutes; discharge at 0.1C for 3 hours until the battery state of charge is 70% SOC (record the corresponding discharge end voltage value U1), and discharge at 1C for 1 second (record the corresponding discharge end voltage value U2). Among them, "1C" is the current value that completely discharges the battery capacity within 1 hour. The DCR of the battery at 70% SOC is calculated according to the following formula: DCR = (U1-U2) / (1C-0.1C).

[0093] 5. Rate performance test

[0094] In an environment of 25℃, the battery was discharged to 3V at a constant current, and the first charge and discharge were performed. Constant current charging was performed at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then constant current discharge was performed at a discharge current of 0.2C until the final voltage was 3V. At this time, the discharge capacity of 0.2C was recorded, and then the battery was repeatedly charged at a charging current of 0.7C until the upper limit voltage was 4.48V, and then constant voltage charging was performed to 0.05C, and then the discharge rate was set to 3C constant current discharge until the final voltage was 3V, and the discharge capacity of 3C was recorded at this time.

[0095] 3C discharge capacity retention rate = (3C discharge capacity / 0.2C discharge capacity) × 100%

[0096] Table 1

[0097]

[0098]

[0099]

[0100] Table 2

[0101]

[0102]

[0103] Tables 1 and 2 show the preparation parameters and performance test results of Examples 1 to 15 and Comparative Examples 1 to 3, and the ratios in the tables are all mass ratios.

[0104] Please refer to Table 1 and Table 2. The difference between the number of weight loss peaks of the first region of the negative electrode at 200°C to 800°C and the number of weight loss peaks of the second region of the negative electrode at 200°C to 800°C in Examples 1 to 15 is not less than 1. The difference between the number of weight loss peaks of the first region of the negative electrode at 200°C to 800°C and the number of weight loss peaks of the second region of the negative electrode at 200°C to 800°C in Comparative Examples 1 to 3 is 0. The AC resistance and DC resistance of Examples 1 to 15 are both less than those of Comparative Examples 1 to 3, and the 3C discharge capacity retention rate is higher than that of Comparative Examples 1 to 3. This may be because when the difference in the number of thermal weight loss peaks between the first region and the second region at 200°C to 800°C is ≥1, the second region has better conductivity, and ions and electrons can easily pass through the second region to reach the first region, thereby improving the kinetic performance of the pole piece.

[0105] Please refer to Examples 1 to 3. As the number of weight loss peaks in the first region of the negative electrode changes from 200°C to 800°C, the AC resistance, DC resistance and 3C discharge capacity of the lithium-ion battery are still better than those in Comparative Examples 1 to 3. It can be seen that as long as the difference in the number of weight loss peaks between the first region and the second region is not less than 1, the above-mentioned technical effects of the present application can be achieved.

[0106] In Comparative Examples 1 to 3, the conductive agent content in the first region is higher than that in the second region, resulting in poor conductivity in the second region, affecting the transmission of electrons and ions from the second region to the first region, and affecting the kinetic performance. In Examples 1 to 12, the conductive agent content in the second region is higher than that in the first region, which is beneficial to improving the kinetic performance.

[0107] Please refer to Examples 1, 4 to 6, which show the effects of different binder compositions. It can be seen that different binders have a certain influence on the DC resistance, AC resistance and 3C discharge capacity retention rate of lithium-ion batteries. When the binder is styrene acrylate and lithium carboxymethyl cellulose, the performance of the lithium-ion battery is optimal.

[0108] Please refer to Examples 7 to 9 and 11 to 12, which show the effect of changes in the mass percentage of the binder in the first region of the negative electrode on lithium-ion batteries. As the mass percentage of the binder increases, the thermogravimetric mass change of the first region at 200°C to 800°C increases. This is because the binder decomposes and oxidizes during the thermogravimetric analysis process, the AC resistance and DC resistance increase, and the 3C discharge capacity retention rate decreases. This is because the presence of the binder hinders the transmission of ions and electrons and reduces conductivity.

[0109] Examples 9 and 10 show that, when the composition of the binder remains unchanged, changing the composition ratio of the binder can affect the performance of the lithium-ion battery.

[0110] In Examples 13 to 15, the time and / or temperature of the heat treatment of the negative electrode are appropriately adjusted so that the number of weight loss peaks of the second region of the negative electrode at 200°C to 800°C is different from that of Examples 2, 3 and 11. It shows that when the number of weight loss peaks of the second region of the negative electrode at 200°C to 800°C is controlled to be 0, the performance of the lithium-ion battery is optimal.

[0111] Table 3

[0112]

[0113]

[0114] Table 4

[0115]

[0116]

[0117] Tables 3 and 4 show the preparation parameters and performance test results of Examples 8, 20 to 27, and the proportions in the tables are all mass ratios.

[0118] Please refer to Examples 8, 16 to 19, which show the influence of the thickness of the negative electrode active material layer. As the thickness of the negative electrode active material layer increases, the AC resistance and DC resistance of the lithium-ion battery increase, and the 3C discharge capacity retention rate decreases. This is because the increase in thickness leads to an increase in ion and electron transmission paths, which reduces the kinetic performance. However, when the thickness of the negative electrode active material layer is too low, it carries too little negative electrode active material, which is not conducive to energy density.

[0119] Please refer to Examples 8, 20 to 23, which show the influence of the thickness of the positive electrode active material layer. Similar to the negative electrode, when the thickness of the positive electrode active material increases, the DC resistance and AC resistance will also increase, and the 3C discharge capacity retention rate will be reduced. However, if the positive electrode active material layer is too small, it will also affect the energy density.

[0120] Please refer to Examples 8, 24 to 27, which show the influence of the composition of the negative electrode active material layer. It can be seen that the negative electrode material selected from silicon dioxide, lithium cobalt oxide, graphite, silicon or hard carbon can achieve good results, but when different negative electrode materials are selected, the compaction density of the negative electrode active material layer is different, among which the comprehensive performance is better when the negative electrode material is graphite.

[0121] Table 5

[0122]

[0123]

[0124] Table 6

[0125]

[0126]

[0127] Tables 5 and 6 show the preparation parameters and performance test results of Examples 8, 28 to 36, and the proportions in the tables are all mass ratios.

[0128] Please refer to Examples 8, 28 to 29, which show the effect of the mass percentage of the conductive agent in the negative electrode active material layer. As the mass percentage of the conductive agent increases, the DC resistance and the AC resistance both decrease, and the 3C discharge capacity retention rate increases. This is because the conductive agent improves the overall conductivity of the negative electrode active material layer. However, when the mass percentage of the conductive agent is too high, it will cause the energy density of the lithium-ion battery to decrease.

[0129] Please refer to Examples 8, 30 to 31, which show the influence of the distribution of the conductive agent in the negative electrode active material layer. It can be seen that when (AB) / B is greater than 20%, the DC resistance and AC resistance can be significantly reduced and the rate performance can be improved. This is because the conductive agent content in the second region is increased, which enables ions and electrons to be transferred to the first region, thereby improving the kinetic performance.

[0130] Please refer to Examples 8, 32 to 36, which show the influence of the type of conductive agent in the negative electrode active material layer. When the conductive agent is conductive carbon black, acetylene black, Ketjen black, carbon nanotubes, graphene or carbon fiber, the performance of the lithium-ion battery is better, among which the performance is best when the conductive agent is carbon nanotubes.

[0131] Table 7

[0132]

[0133]

[0134] Table 8

[0135]

[0136]

[0137] Tables 7 and 8 show the preparation parameters and performance test results of Examples 37 to 49. The proportions in the tables are all mass ratios. Examples 37 to 49 all subjected the positive electrode to heat treatment, and Example 49 subjected both the positive and negative electrodes to heat treatment.

[0138] Please refer to Examples 37 to 41, which show the influence of the compaction density of the positive electrode active material layer. As the compaction density of the positive electrode active material layer increases, the AC resistance and DC resistance increase, and the 3C discharge capacity retention rate decreases. This is because the increase in compaction density leads to an increase in the positive electrode material per unit volume, which reduces the wettability of the electrolyte and reduces the kinetic performance.

[0139] Please refer to Examples 42 to 44, which show the influence of the thickness of the positive electrode active material layer. As the thickness of the positive electrode active material layer increases, the kinetic performance decreases, the resistance increases, and the rate performance deteriorates.

[0140] Please refer to Examples 45 to 48, which show the influence of the positive electrode active material. The active materials used in these examples all have good performance, and when the active material is lithium cobalt oxide, the comprehensive performance is better. In Example 49, the positive electrode and the negative electrode are heat treated at the same time, so that the positive electrode and the negative electrode have good kinetic performance, the AC resistance and DC resistance are the smallest, and the 3C discharge performance is the best.

[0141] The above description is only a preferred embodiment of the present application and an explanation of the technical principles used. Those skilled in the art should understand that the scope of disclosure involved in the present application is not limited to the technical solution formed by a specific combination of the above technical features, but should also cover other technical solutions formed by any combination of the above technical features or their equivalent features. For example, the above features are replaced with the technical features with similar functions disclosed in the present application.

Claims

1. An electrode, characterized in that: include: A current collector and an active material layer located on one side or both sides of the current collector; the active material layer includes a first region and a second region, and along the thickness direction of the electrode, the first region is located between the current collector and the second region; the first region is from the current collector side to 2 / 3 of the thickness of the active material layer, and the second region is from 2 / 3 of the thickness of the active material layer to the surface of the electrode; The active material layer is subjected to thermogravimetric analysis at a heating rate of 10° C. / min under an inert atmosphere. The result of the thermogravimetric analysis shows that the difference in the number of thermal gravimetric peaks between the first region and the second region at 200° C. to 800° C. is ≥1.

2. The electrode according to claim 1, characterized in that The active material layer is subjected to thermogravimetric analysis at a heating rate of 10°C / min under an inert atmosphere. The results of the thermogravimetric analysis show that the number of weight loss peaks in the first region from 200°C to 800°C is not less than 1, and the number of weight loss peaks in the second region from 200°C to 800°C is 0 to 2.

3. The electrode according to claim 1, characterized in that Satisfy at least one of the following: (a) the thermogravimetric analysis results show that the mass change of the first region from 200° C. to 800° C. is 0.21% to 13%; (b) The results of the thermogravimetric analysis show that the mass change of the second region from 200° C. to 800° C. is 0% to 2.4%.

4. The electrode according to claim 1, characterized in that The results of the thermogravimetric analysis show that the mass change of the first region at 200° C. to 800° C. is 1.6% to 4.02%.

5. The electrode according to claim 1, characterized in that The electrode is a negative electrode, the active material layer is a negative electrode active material layer, and the current collector is a negative electrode current collector.

6. The electrode according to claim 5, characterized in that The electrode satisfies at least one of the following conditions: (c) The compaction density of the negative electrode active material layer is ρ1≥0.6 g / cm 3 ; (d) the thickness h1 of the negative electrode active material layer on one side of the negative electrode current collector is ≥ 10 μm; (e) The negative electrode active material layer includes a negative electrode material, and the negative electrode material includes at least one of lithium titanate, silicon oxide, graphite, silicon or hard carbon.

7. The electrode according to claim 5, characterized in that The electrode satisfies at least one of the following conditions: (f) The compaction density ρ1 of the negative electrode active material layer satisfies: 1.85 g / cm 3 ≥ρ1≥0.65g / cm 3 ; (g) The thickness h1 of the negative electrode active material layer on one side of the negative electrode current collector satisfies: 1500 μm ≥ h1 ≥ 15 μm.

8. The electrode according to claim 5, characterized in that The electrode satisfies at least one of the following conditions: (h) The compaction density ρ1 of the negative electrode active material layer satisfies: 1.83 g / cm 3 ≥ρ1≥1.0g / cm 3 ; (i) The thickness h1 of the negative electrode active material layer on one side of the negative electrode current collector satisfies: 150 μm ≥ h1 ≥ 30 μm.

9. The electrode according to claim 1, characterized in that The electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the electrode satisfies at least one of the following conditions: (j) The compaction density of the positive electrode active material layer ρ2≥2g / cm 3 ; (k) the thickness h2 of the positive electrode active material layer on one side of the positive electrode current collector is ≥ 20 μm; (l) The positive electrode active material layer includes a positive electrode material, and the positive electrode material includes at least one of lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium manganese oxide, lithium cobalt oxide or lithium nickel cobalt aluminum oxide.

10. The electrode according to claim 1, characterized in that The electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the electrode satisfies at least one of the following conditions: (m) The compaction density ρ2 of the positive electrode active material layer satisfies: 4.25 g / cm 3 ≥ρ2≥2.3g / cm 3 ; (n) The thickness h2 of the positive electrode active material layer on one side of the positive electrode current collector satisfies: 1500 μm ≥ h2 ≥ 30 μm.

11. The electrode according to claim 1, characterized in that The electrode is a positive electrode, the current collector is a positive electrode current collector, the active material layer is a positive electrode active material layer, and the electrode satisfies at least one of the following conditions: (o) The compaction density ρ2 of the positive electrode active material layer satisfies: 4.23 g / cm 3 ≥ρ2≥4.0g / cm 3 ; (p) The thickness h2 of the positive electrode active material layer on one side of the positive electrode current collector satisfies: 130 μm ≥ h2 ≥ 26 μm.

12. The electrode according to claim 1, characterized in that The active material layer includes a conductive agent and satisfies at least one of the following: (q) the mass percentage of the conductive agent in the first region is B, the mass percentage of the conductive agent in the second region is A, and A is greater than B; (r) the mass percentage of the conductive agent in the first region is B, the mass percentage of the conductive agent in the second region is A, (A-B) / B≥20%; (s) the conductive agent comprises at least one of carbon nanotubes, carbon fibers, acetylene black, graphene, Ketjen black or conductive carbon black; (t) The conductive agent has a content of 0 to 2% by mass in the active material layer based on the total mass of the active material layer.

13. The electrode according to claim 1, characterized in that The first region includes a polymer compound and satisfies at least one of the following conditions: (u) the polymer compound comprises at least one of polyethylene oxide, polypropylene oxide, polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyimide, polysiloxane, polyacrylic acid, polypropylene derivatives, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, polymethyl pyrrolidone, polyvinyl pyrrolidone, styrene acrylate or styrene-butadiene rubber; (v) The mass percentage of the polymer compound in the active material layer is 0.42% to 14%.

14. The electrode according to claim 1, characterized in that The first region includes a polymer compound, and the mass percentage of the polymer compound in the active material layer is 2.0% to 5.0%.

15. A method for preparing an electrode according to any one of claims 1 to 14, characterized in that: include: Applying the slurry of the active material layer to at least one surface of the current collector, drying, and cold pressing to obtain an initial electrode; Processing the initial electrode to obtain the electrode; Wherein, processing the initial electrode comprises: The initial electrode is subjected to plasma treatment in a vacuum environment, wherein the plasma power is 0.5 kW to 5 kW, the gas source comprises at least one of nitrogen, argon or carbon tetrafluoride, the gas flow rate is 3000 sccm to 5000 sccm, the temperature is 20° C. to 60° C., and the treatment time is 0.5 min to 1 min; or, Heat treating the initial electrode in a vacuum or inert gas environment at a temperature greater than 200° C. for a time of 1 to 3 minutes; or, The initial electrode is laser bombarded in a vacuum or inert gas environment, with a laser intensity of 30W to 100W and a processing time of 0.5s to 1s.

16. A method for preparing an electrode according to any one of claims 1 to 14, characterized in that: include: Applying the slurry of the active material layer to at least one surface of the current collector, drying, and cold pressing to obtain an initial electrode; Processing the initial electrode to obtain the electrode; Wherein, processing the initial electrode comprises: The initial electrode is heat treated in a vacuum or inert gas environment, the heat treatment temperature is 350° C. to 600° C., and the heat treatment time is 1 min to 3 min.

17. An electrochemical device, characterized in that: including electrodes; The electrode is the electrode according to any one of claims 1 to 14; or The electrode is an electrode prepared by the preparation method described in any one of claims 15 to 16.

18. An electronic device, characterized in that: Comprising the electrochemical device as claimed in claim 17.

Citation Information

Patent Citations

  • Silicon electrode thermally treated by adopting one-step method

    CN104393238A